Process modeling toward higher degradation and minimum energy consumption of an electrochemical decontamination of food dye wastewater - Hussain, Sajjad (2021)
This study explores the modeling and optimization of electrochemical influencing parameters on the sunset yellow (SSY) decontamination process by response surface methodology (RSM). Four factors historical data design which include time (X1), pH 03–10​ (X2), NaCl concentration 0.02–0.08 M (X3) and current densities 2.5 to 10 mA cm −2 (X4) was employed to correlate the factors with dye removal and electrical energy consumption as responses. Stepwise regression analysis of first order, second order, cubic and quadratic polynomial models were performed to test the model fitness. Higher degradation of SSY at examined array was found to 99.2% with energy consumption of 0.340 kWhm−3 and the operating variables were as follows: time: 48.42 min, pH of 4.15, NaCl concentration of 0.065 M and current density of 2.70 mA cm −2. The model for energy consumption fitted with experimental data demonstrated a higher R2 value of 0.9998, proving the significance of proposed model. The Analysis of variance (ANOVA) with a higher value of R2: 0.9746 adjusted R2: 0.9716, predicted R2: 0.9639 and t-test revealed that second-order polynomial model fitted the experimental results well and have a decent correlation between the observed and predicted data of SSY degrdation. Furthermore, the degradation process followed pseudo first order kinetic under different operating parameters and 53% TOC (total organic carbon) removal as observed as consequence of electrochemical degradation of SSY at optimized conditions. The results revealed that the historical data design response surface methodology is worth statistical tools for accuratley predicting the optimum conditions for electrochemical abatement of food dye sunset yellow.